Efectos del consumo de Alimentos transgénicos sobre la caries en población de adultos: una revisión sistemática (2023)
Transgenic foods have revolutionized different areas of health, Sincé they can carry key genetic information for immunological action against diseases such as caries; the present study had as objective to determine the effects of the consumption of transgenic foods on caries in adult population from a descriptive methodology and systematic review type in which the prism method was used and the application of equations constructed by means of key words and Boolean connectors, which were entered to the bibliographic search engines, a total of 11 articles were filtered which indicated results an immune effect especially in probiotic foods for the prevention of caries; other foods such as genetically modified saturated fats can have negative effects. The study concludes that further research should be carried out in order to identify the immune information that these foods may carry against streptococcus mutans.